Technology and nursing practice - a bibliographical research - Emeline Moura Lopes; Ana Karina Bezerra Pinheiro; Patrícia Neyva Costa Pinheiro; Neiva Francenelly Cunha Vieira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
The study aimed to analyze the scientific production related to the use of technology in the practices of nursing. This is a bibliographic study of quantitative approach, which used to search in the databases Scielo, LILACS, Medline and BDEnf, in which the descriptors used were technology and educational technology. Twenty-eight articles were selected. Most of the articles, 27 (96.4%), had been published in journals inside the nursing area. It was observed that the articles with the chosen thematic had been published from 2000 onwards. Among the studies, sixteen (57.1%) are related to the development, implementation experience or reports of the use of technologies. Of these, 10 (62.5%) were targeted to own professionals and five (31.2%) towards the patients. As for the type of technology, 11 (68.7%) used harsh technologies. It is perceived the greater interest of nurses in developing and using technology in their practice in the past five years. This consists as a facilitator methodology for the nursing profession and as a benefit for the nursing's actions improvement.